Architettura come immagine, rapporto e trasformazione: una ricerca collettiva sul pensiero di Massimo Fagioli - Ciampelletti, Isa Giovanna; Calzini, Caterina; Vitale, Flavio; Montanino, Veronica; Panzera, Anna Maria; Durante, Daniele; Casciaro, Alice (Il sogno della farfalla, 2025)
A recent monographic issue of Arc2città (19, 2024) dedicated entirely to Massimo Fagioli compiles contributions from architects and scholars regarding the projects developed by the psychiatrist in collaboration with a group of architects. This collective, known as “Il coraggio delle immagini” (“The courage of images”) and formed within the framework of the Collective Analysis (Analisi collettiva), worked throughout the 1990s and 2000s on a diverse range of projects — from individual furniture pieces to residences and entire city districts. Rooted in the dialogue between Fagioli’s Human Birth Theory and architectural design practice, this experience produced works, exhibitions, and conferences that challenged functionalism and typological conformity, paving the way for a new form of creativity grounded in non-conscious psychic realities. The revised contributions presented here trace this history, exploring architecture as a collective and transformative act. They also highlight the distinctiveness of an architectural practice inspired by the psychiatrist’s theory and praxis, developed through direct collaboration with him. In this conception, architecture becomes a critical tool against the dominant culture and a privileged space for expressing a new vision of dwelling and human existence — one capable of integrating inner psychological dimensions with public life.